A systems‐engineering approach to nation‐scale problems: Municipal solid waste management in Saudi Arabia. Issue 6 (13th August 2021) - Midgley, W. J. B.; Henshaw, M. J. de C.; Alshuhri, S.
Abstract: The systems‐engineering context of the solid waste disposal problem is discussed with a focus on the issues in Saudi Arabia. A methodology was developed for dividing the system of interest into a set of weakly‐coupled sub‐systems that interact with the narrow system of interest. A model of the narrow system of interest, in this case the municipal solid waste (MSW) system of Saudi Arabia, was then created and validated. The development of this mathematical model is described and is used to investigate a range of scenarios for the future of Saudi Arabia's MSW system with a time horizon of 30 years. The most effective method uses anaerobic digestion, incineration and recycling to reduce the total mass to landfill over the 30 years by 73% when compared to the default scenario (no action taken). In the final year of the simulation, this method reduces the total annual mass to landfill by 69% when compared to a reasonable source reduction strategy. The energy generated by incineration, is shown to contribute a maximum of 2.3% to the Kingdom's annual energy production. Lifecycle analysis shows that the best waste management method produces a DALY (disability life year) score which is 2% of the current strategy, even if moderate source reduction is employed. The two newly suggested scenarios are shown to have a net positive impact on the environment due to the recycling of a large part of the waste stream, preventing acidification/eutrophication due to the manufacture of virgin goods.